WATCH: 'Gender Queer' And 'All Boys Aren't Blue' Excerpts QUOTED During Senate Hearing On BOOK BANS - The Hill (2023)
A Senate Judiciary Committee hearing on book bans took a racy turn Tuesday, as Republican senators and a witness read scenes of various sexual content into the congressional record to defend the banning of multiple titles from U.S. schools. Read more: https://thehill.com/homenews/educatio...